PWE-039 Routine water soluble contrast swallow has limited clinical value in the detection of anastomotic leaks following oesophagectomy. (28th May 2012) - Love, S; Bruce, S; Athwal, T S; Howes, N; Hartley, M
Abstract : Introduction: Water-soluble contrast swallow (WSCS) is performed following oesophagectomy to assess anastomotic integrity before commencing oral intake. This study, the largest in the UK to date, challenges the routine use of WSCS following oesophagectomy. Methods: All patients undergoing open transthoracic oesophagectomy for oesophageal cancer with intrathoracic anastomosis, within a supra-regional upper GI cancer centre, were registered on a prospective database between 2006 and 2011. WSCS results, anastomotic leak rate and the modality of leak detection were analysed. Results: During the study period, 116 oesophagectomies were performed. WSCS was undertaken in 97 (84%) cases on a median of day 5 (range 3–8) post operatively; 95 (98%) WSCS reported no evidence of a leak, two studies reported a leak and one study was equivocal. WSCS was not performed in 19 (16%) cases; 10 patients developed early clinical signs suggestive of an anastomotic leak and were immediately imaged by CT, eight had a prolonged ITU stay due to cardiorespiratory complications while one patient died peri-operatively. There were 6 (5%) anastomotic leaks of which three patients had immediate CT due to clinical deterioration while three patients had routine WSCS. WSCS was followed by CT in two patients due to a positive or equivocal finding. One patient had no WSCS evidence of a leak but then developed sepsis and CT confirmed a leak. Clinical signs suggestive of a leak were evident in all patients within 7 days post-operatively. Conclusion: Routine WSCS has limited value in the detection of anastomotic leak following oesophagectomy. All patients with an anastomotic leak developed significant clinical signs of a leak that were subsequently confirmed by CT imaging. WSCS altered the management in just 2% of cases. Competing interests: None declared.